Plumbagin Protects Against Spinal Cord Injury-induced Oxidative Stress and Inflammation in Wistar Rats through Nrf-2 Upregulation - Zhang, W.; Cheng, L.; Hou, Y.; Si, M.; Zhao, Y.-P.; Nie, L. (Drug Research, 2015)
Background: Spinal cord injury causes post-traumatic degeneration through series of biochemical events. This study aims to evaluate the possible protective mechanism of Plumbagin against Spinal cord injury induced oxidative stress and inflammation. Plumbagin is a potent antioxidant and shows anti-carcinogenic, anti-inflammatory and analgesic activities. However, its exact molecular mechanism of action has yet to be explored.Methods: We tested the effects of Plumbagin on spinal cord injury induced ROS generation and lipid peroxidation content in wistar rats. Additionally, the expression of 2 important transcription factors NF-κB and Nrf-2 was investigated.Results: Plumbagin treatment significantly ameliorated oxidative stress through inhibition of ROS and lipid peroxidation with a concomitant increase in antioxidant status. Western blot analysis revealed enhanced nuclear levels of Nrf-2, while NF-κB expression was suppressed during Plumbagin administration. Enzyme linked immunosorbent assay for pro-inflammatory cytokines (TNF-α, IL-1β) showed a significant downregulation followed by Plumbagin treatment in spinal cord injury rats.Conclusion: Taken together, the data suggests potential and novel role of Plumbagin in cytoprotection by modulating NF-κB and Nrf-2 levels against spinal cord injury.
Keywords: cytokines; reactive oxygen species; antioxidant; neuroprotection